Feminist economic geography and the future of work. (October 2020) - Reid-Musson, Emily; Cockayne, Daniel; Frederiksen, Lia; Worth, Nancy
Scholars have recently begun to account for the absence of feminist analyses in the popular and academic discourse surrounding 'the future of work'. In this article we offer a critical synthesis of emerging research from feminist economic geography to propose a series of questions about the future of work, conceptualized as both an object of intellectual inquiry and an emerging empirical reality. Feminist economic geography emphasizes difference, embodiment, and conceives of workplaces as dynamic, uneven, and untidy spaces, an emphasis which can help recenter discussions about the future of work on workers and their experience of work. Our discussion features a series of analytically rigorous, theoretically informed, and empirically rich conference papers, organized around three critical questions: Who are the subjects of the future of work? What counts as work? And where should we look? We highlight a broad concept of work developed through debates among feminist scholars across disciplinary fields as a key frame for understanding the global economy, including difference, social reproduction, and the spatial division of labor. Feminist economic geographers are pluralizing the subjects, forms, and geographies of work, which may help enhance our understanding of the future of work in economic geography.